The stranger inside - Unger, Lisa, 1970- (Park Row Books, 2019)
"Twelve-year-old Rain Winter narrowly escaped an abduction while walking to a friend's house. Her two best friends, Tess and Hank, were not as lucky. Tess never came home, and Hank was held in captivity before managing to escape. Their abductor was sent to prison but years later was released. Then someone delivered real justice and killed him in cold blood. Now Rain is living the perfect suburban life, her dark childhood buried deep ... But when another brutal murderer who escaped justice is found dead, Rain is unexpectedly drawn into the case"--Dust jacket flap.